Electron-induced fragmentation of water droplets: Simulation study - Suchan, Jiří; Kolafa, Jiří; Slavíček, Petr (The Journal of chemical physics, 2022)
The transport of free electrons in a water environment is still poorly understood. We show that additional insight can be brought about by investigating fragmentation patterns of finite-size particles upon electron impact ionization. We have developed a composite protocol aiming to simulate fragmentation of water clusters by electrons with kinetic energies in the range of up to 100 eV. The ionization events for atomistically described molecular clusters are identified by a kinetic Monte Carlo procedure. We subsequently model the fragmentation with classical molecular dynamics simulations, calibrated by non-adiabatic quantum mechanics/molecular mechanics simulations of the ionization process. We consider one-electron ionizations, energy transfer via electronic excitation events, elastic scattering, and also the autoionization events through intermolecular Coulombic decay. The simulations reveal that larger water clusters are often ionized repeatedly, which is the cause of substantial fragmentation. After losing most of its energy, low-energy electrons further contribute to fragmentation by electronic excitations. The simultaneous measurement of cluster size distribution before and after the ionization represents a sensitive measure of the energy transferred into the system by an incident electron.
Keywords: Electrons; Computer Simulation; Monte Carlo Method; metoda Monte Carlo; Water; počítačová simulace; přenos energie; elektrony; voda; Energy Transfer